Hand hygiene compliance and associated factor among nurses working in public hospitals of Hararghe zones, Oromia region, eastern Ethiopia - Hamza Umar; Abraham Geremew; Teshager Worku Kassie; Gebisa Dirirsa; Kefelegn Bayu; Dechasa Adare Mengistu; Ashenafi Berhanu; Salie Mulat (Frontiers Media S.A., 2022)
BackgroundHealthcare workers are in constant contact with a wide variety of materials and surfaces, including waste, body fluids, mucous membranes, food, their own bodies, and the skin of patients. As a result, their hands are colonized by different groups of pathogens. Hand hygiene of healthcare workers is recognized to be the main factor in reducing healthcare-associated infections. Therefore, this study aimed to assess hand hygiene adherence and related factors among nurses working in public hospitals in eastern Ethiopia.MethodsAn institutional based cross-sectional study was conducted in Hospital, Hararghe zone, Eastern Ethiopia from July 1 to 30, 2021. A total of 451 study participants were randomly selected, after the proportional allocation of study participants to each selected hospital. The data was collected using self-administered questionnaire and observation checklist. SPSS version 26 was used to analyze the data. Bivariable and multivariable analysis were employed to assess the association between outcome and independent variables. Finally, a p-value of < 0.05 was used as a cutoff point for statistical significance.ResultsOut of 436 eligible nurses, the overall hand hygiene compliance was 37.4% [95% CI (0.33, 0.42)]. The overall compliance among those working in medical, surgical, OR ward, OPD, Gynecology/obstetrics, emergency ward, Intensive care units, Pediatrics, and other wards/departments was 46.8, 44.8, 35.7, 28.2, 20.7, 45.1, 23.1, 40.5, and 29.4%, respectively. The mean knowledge score was 21.6% (SD: 2.08). Furthermore, there was a statistically significant association between hand hygiene compliance and gender, work experience, training in hand hygiene, availability of running water, and knowledge of hand hygiene.ConclusionThe current study found overall compliance with hand hygiene accounted for 34.7%. Therefore, an exemplary worker may initiate others to do so, and strong managerial and leadership commitment may also help the workers stick to the rules and regulations to follow the multimodal hand hygiene practice as per WHO recommendation.